Interactive Verifiable Secret Sharing Scheme - O. V. Kazarin (Безопасность информационных технологий, 2010)
Commitment schemes, secret sharing schemes, interactive zero-knowledge proofs which underlie the offered interactive secrete sharing schemes are considered. Such schemes are one of the main computing primitives in the theory of secure computations. Base elements of the theory of secure computations and schemes of construction of synchronous verifiable secrete sharing as schemes of secure function evaluation are resulted.